Electrical stimulation of the frontal cortex enhances slow-frequency EEG activity and sleepiness. (2nd June 2016) - D'Atri, A.; De Simoni, E.; Gorgoni, M.; Ferrara, M.; Ferlazzo, F.; Rossini, P.M.; De Gennaro, L.
Highlights: 5 Hz more than 0.8 Hz anodal tDCS is effective in inducing EEG synchronization. 5 Hz anodal tDCS as compared to sham induces an enhancement of sleepiness. Cortical topography of delta EEG changes is regionally related to sleepiness. Abstract: Our aim was to enhance the spontaneous slow-frequency EEG activity during the resting state using oscillating transcranial direct currents (tDCS) with a stimulation frequency that resembles the spontaneous oscillations of sleep onset. Accordingly, in this preliminary study, we assessed EEG after-effects of a frontal oscillatory tDCS with different frequency (0.8 vs. 5 Hz) and polarity (anodal, cathodal, and sham). Two single-blind experiments compared the after effects on the resting EEG of oscillatory tDCS [Exp. 1 = 0.8 Hz, 10 subjects (26.2 ± 2.5 years); Exp. 2 = 5 Hz, 10 subjects (27.4 ± 2.4 years)] by manipulating its polarity. EEG signals recorded (28 scalp derivations) before and after stimulation [slow oscillations (0.5–1 Hz), delta (1–4 Hz), theta (5–7 Hz), alpha (8–12 Hz), beta 1 (13–15 Hz) and beta 2 (16–24 Hz)] were compared between conditions as a function of polarity (anodal vs. cathodal vs. sham) and frequency of stimulation (0.8 vs. 5 Hz). We found a significant relative enhancement of the delta activity after the anodal tDCS at 5 Hz compared to that at 0.8 Hz. This increase, even though not reaching the statistical significance compared to sham, is concomitant to a significant increase of subjective sleepiness, as assessed by a visual analog scale. These two phenomena are linearly related with a regional specificity, correlations being restricted to cortical areas perifocal to the stimulation site. We have shown that a frontal oscillating anodal tDCS at 5 Hz results in an effective change of both subjective sleepiness and spontaneous slow-frequency EEG activity. These changes are critically associated to both stimulation polarity (anodal) and frequency (5 Hz). However, evidence of frequency-dependence seems more unequivocal than evidence of polarity-dependence.